The Effect of Atopic Dermatitis and Diet on the Skin Transcriptome in Staffordshire Bull Terriers - Anturaniemi, Johanna; Zaldívar-López, Sara; Savelkoul, Huub F. J.; Elo, Kari; Hielm-Björkman, Anna (Frontiers in Veterinary Science, 2020)
Canine atopic dermatitis (CAD) has a hereditary basis that is modified by interactions with the environment, including diet. Differentially expressed genes in non-lesional skin, determined by RNA sequencing before and after a dietary intervention, were compared between dogs with naturally occurring CAD (n=4) and healthy dogs (n=4). The dogs were fed either a common commercial heat-processed high carbohydrate food (kibble diet) (n=4), or a non-processed high fat food (raw meat-based diet) (n=4). At the end of the diet intervention, 149 differentially expressed transcripts were found between the atopic and healthy dogs. The main canonical pathways altered by the dysregulation of these genes were angiopoietin signaling, epidermal growth factor signaling, activation of angiogenesis, and alterations in keratinocyte proliferation and lipid metabolism. On the other hand, 33 differently expressed transcripts were found between the two diet groups, of which 8 encode genes that are annotated in the current version of the dog genome: immunoglobulin heavy constant mu (IGHM), immunoglobulin lambda-like polypeptide 5 (IGLL5), B-cell antigen receptor complex-associated protein beta chain (CD79B), polymeric immunoglobulin receptor (PIGR), cystathione β-synthase (CBS), argininosuccinate synthase 1 (ASS1), secretory leukocyte peptidase inhibitor (SLPI), and mitochondrial ribosome recycling factor (MRRF). All genes were upregulated in the raw diet group. In conclusion the findings of this study suggest alterations in lipid and keratinocyte metabolism as well as angiogenesis in the skin of atopic dogs. Additionally, a possible enhancement of innate immunity and decrease in oxidative stress was seen in raw food fed dogs, which could have an important role in preventing hypersensitivities and disturbed immunity at young age.